2015
DOI: 10.1074/jbc.m114.575217
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Apoptosis Induced by Selective Inhibition of Rac GTPase versus Global Suppression of Rho Family GTPases Is Mediated by Alterations in Distinct Mitogen-activated Protein Kinase Signaling Cascades

Abstract: Background: Rac GTPase is essential for the survival of primary cerebellar granule neurons (CGNs). Results: NSC23766-mediated Rac inhibition induces CGN apoptosis through deactivation of prosurvival MEK5/ERK5 signaling. Conclusion: Targeted inhibition of Rac versus global inhibition of Rho GTPases induces apoptosis via disruption of unique MAP kinase signaling pathways. Significance: Elucidating the pathways that mediate neuronal apoptosis is critical for understanding the pathology of neurodegenerative diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Impaired differentiation and apoptosis have been reported in Rac1-KO telencephalon-derived neurons (Chen et al, 2009). In addition, selective inhibition of Rac has been reported to induce apoptosis in CGNs (Stankiewicz et al, 2015). Rac1/Rac3-DKO CGNs exhibited: (1) a normal pattern of differentiation until the expression of NeuN, a marker for postmitotic CGNs, was seen in the deepest layer of the EGL at P5; (2) few Map2-positive neurites in cerebellar microexplants and disrupted development of vertical dendrites at P8; and (3) robust apoptosis at the deep layer of the EGL, a premigratory zone for preparing the subsequent radial migration (Yamasaki et al, 2001), at P8.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired differentiation and apoptosis have been reported in Rac1-KO telencephalon-derived neurons (Chen et al, 2009). In addition, selective inhibition of Rac has been reported to induce apoptosis in CGNs (Stankiewicz et al, 2015). Rac1/Rac3-DKO CGNs exhibited: (1) a normal pattern of differentiation until the expression of NeuN, a marker for postmitotic CGNs, was seen in the deepest layer of the EGL at P5; (2) few Map2-positive neurites in cerebellar microexplants and disrupted development of vertical dendrites at P8; and (3) robust apoptosis at the deep layer of the EGL, a premigratory zone for preparing the subsequent radial migration (Yamasaki et al, 2001), at P8.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway plays an important role in regulating neuronal survival and inhibiting neuronal apoptosis [43, 44]. Rac1 has been shown to promote cell survival via Akt [45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that Rac acts as an upstream activator of JNK/c-Jun signaling [9,16,17], while others have suggested that Rac can also suppress the JNK pathway [10,18]. To expand our current studies related to the inhibition of Rac activity and its relation to apoptosis in OSC-19 and HOC313 cells, we investigated downstream signaling of the Rac pathway.…”
Section: Resultsmentioning
confidence: 99%
“…One mechanism that requires additional elucidation is the regulation of JNK activity after suppression of Rac. Many studies have indicated that Rac acts as an upstream activator of JNK signaling in certain cells [9,16,17], while others have reported that Rac can suppress the JNK pathway [10,18]. In general, whether Rac positively or negatively regulates the JNK pathway may primarily depends on the specific cancer cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation